A new freshwater teleosaurid from the Jurassic of northeastern Thailand. Issue 6 (2nd November 2018) - Martin, Jeremy E.; Suteethorn, Suravech; Lauprasert, Komsorn; Tong, Haiyan; Buffetaut, Eric; Liard, Romain; Salaviale, Celine; Deesri, Uthumporn; Suteethorn, Varavudh; Claude, Julien
ABSTRACT: The core of the fossil record of Teleosauridae, a family of thalattosuchian crocodylomorphs, is well known from western Tethyan marine deposits of the Jurassic. Outside this province, their fossil record is patchy and in need of revision, with specimens from Russia, Madagascar, and Asia. Peipehsuchus teleorhinus is known from the Early or Middle Jurassic of China and teleosaurid specimens have been mentioned or preliminarily described from two Jurassic localities in Thailand, yet they were not assigned to a given taxon. Thanks to recent field work, at least 10 individuals represented by cranial material were excavated and prepared from a single Jurassic locality known as Phu Noi in the lower Phu Kradung Formation of northeastern Thailand. Here, we describe these specimens, together with disarticulated postcranial elements, and erect a new taxon, Indosinosuchus potamosiamensis, gen. et sp. nov. Phylogenetic analyses confirm the teleosaurid affinities of the new species, which does not form an exclusive clade with the Chinese teleosaurid Peipehsuchus teleorhinus . The presence of teleosaurids at Phu Noi and a preliminary account of its faunal content favor a Middle to Late Jurassic age for the fossil-bearing horizon. In contrast, Cretaceous deposits in Thailand are characterized by goniopholidids and pholidosaurids, indicating a faunal turnover in Southeast Asia across the Jurassic–Cretaceous. As previously shown by isotope data, the new teleosaurid species was a resident of the freshwater environment and co-occurs with remains of exclusively terrestrial taxa such as sauropod, ornithopod, and theropod dinosaurs and freshwater tetrapods such as turtles and temnospondyls.